Social media and counterpublic spheres in an authoritarian state: Exploring online political discussions among Cambodian Facebook users. (April 2020) - Chunly, Sereyvicheth
Abstract: Social media have been viewed as an important channel through which dissenting and marginalized voices can be disseminated and discussed in authoritarian political settings, such as Cambodia. Drawing on a case study of viral discussions on Facebook concerning a hit-and-run traffic accident that took place in March 2019 in Cambodia, this paper explores (1) the key themes that arose from the online conversations and whether they constituted counterpublic discourse, (2) the discursive strategies used by online discussants, and (3) the political implications of such online phenomena. Based on a thematic and discourse analysis of 5000 Facebook comments generated from 100 widely shared public posts about the incident, the study uncovered a number of recurrent themes emerging from the online interactions, most of which were critical of the authoritarian establishment. The study also identified three key discursive strategies employed by Facebook users to discuss and question the status quo: satire, direct criticism and rumour. In addition, guided by Fraser (1990) and Warner (2002)'s concepts of "counterpublics" and boyd (2010)'s recent notion of "networked publics", the study argues that, through such online discursive interactions, a new social identity in the form of online counterpublics has been formed.